(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Mangrove ecosystems protect coastlines from abrasion and erosion, dampen strong winds against oceans, and bind sediment periodically. The purpose of the study was to determine the effects of Avicennia marina sedimentation on wave attenuation. The employed methods in this research were spot-check, transect-squared, and laboratory test methods. The measurement of the wave data involved SBE 26 and RBRDuo T.D. They were carried out at 5 stations with thicknesses of 3 m, 5 m, 10 m, 20 m, and 50 m respectively. The percentages of the wave energy attenuation were 49.5%, 53.8%, 82.9%, 91.4%, and 92.3%, with grain diameter percentages of 19.36%, 19.75%, 19.87%, and 21.27%. The higher the percentage of wave attenuation, the smaller the percentage of grains, and vice versa. When a wave arrives, the energy is so large that each large particle of the sediment in the sea is brought back to the mangrove ecosystem. When the wave disappears, the released energy gets so smaller that only small particles are taken back to the sea. The conclusion of this study is that the diameter percentage of mangrove sediment was related to the percentage of wave attenuation. The greater the percentage of wave attenuation, the smaller the percentage of grains.